IMPLEMENTATION OF ARIAS LEARNING MODEL TO IMPROVE STUDENT’S CREATIVE THINKING ABILITY - Iffah Hidayati; Syifa’ul Gummah; Samsun Hidayat (Universitas Pendidikan Mandalika, 2016)
A good teaching process is a teaching that allows student active role or recoqnisa student for their active participation. One of the methods that can be applied in teaching process is ARIAS. This research aims to analyze student creative thinking skill in grade VIII student at SMP Muhammadiyah Mataram. The research implies on class activity observation as research methodology by enacting two cycles. The data of creative thinking skill was collected by using essay test to measure the student skill at the end of the cycle. The result of this research has shown that student creative thinking skill on the first cycle was categorized less-creative with the average of 52,25% and the second cycle was found that creative thinking skill of student has increased and classified as creative with the average of 74,74%. At the conclusion, that the implementation of ARIAS teaching method has enhancad creative thinking skill on the subject of Works and Energy in grade VIII student at SMP Muhammadiyah Mataram, on the academic year of 2015/2016.